Al-Qur’ān wa al-Isti‘mār: Radd al-Shaykh al-Ḥājj Ahmad Sanusi (1888-1950) ‘alá al-Isti‘mār min Khilāl Tafsīr Mal’ja’ al-Ṭālibīn - Rohmana, Jajang A. (Studia Islamika, 2015)
K.H. Ahmad Sanusi played an important role in developing the intellectual traditions of pesantren in Priangan, West Java, Indonesia. Scholars have already  gone some way in describing this role. However, Sanusi’s response to colonialism has, in comparison, almost gone unnoticed. Generally, Sanusi’s works were published while he was in exile, which happened shortly after his return from Mecca. For example, one of his critical works of colonialism was Malja’ Al-Ṭālibīn, a Sundanese Qur’anic exegesis in pegon script which circulated in 1930-1931. In focusing on Sanusi, this article argues that the ‘ulamā’ of pesantren played an important role in embedding influential anti-colonial sentiment in Priangan. This was achieved not only through physical resistance but also through religious publications. Sanusi’s anti-colonial spirit would later influence his interpretation of the Qur’an. His experiences reveal the influence of his pilgrimage to Haramayn in growing a sense of Indonesian nationhood in the early 20th century.DOI: 10.15408/sdi.v22i2.1921